KONSEP SYADZ DAN APLIKASINYA DALAM MENENTUKAN KUALITAS HADIS - Aan Supian (Universitas Islam Negeri Fatmawati Sukarno, 2015)
In various research traditions, rules avoid syadz often overlooked in the application as a rule the validity of hadith. This is due, search around conception syadz including a study of a difficult and rarely done by the scholars of hadith. Therefore understandable if the benchmarks avoid syadz as a rule the validity of hadith has not been formulated systematically and methodologically. This article studies will be directed at the problem: How syadz conception according to hadith scholars? How methodological steps to determine syadz and its application in the study of hadith? and How the formulation of rules to avoid minor syadz as the criterion validity of Matan hadith? Based on the results of the study showed that there was no uniformity of views among scholars about the conception syadz. Especially notable differences occur between three famous hadith scholars, al- Shafi’i, al-Hakim and Abu Ya’la al-Khaliliy. A conception which is often referred to by the majority of scholars of hadith is the opinion of Imam Shafi’i. According to al-Shafi’i a hadith contains syadz only if the hadith narrated by a narrator tsiqat, and violate or contradict the hadith narrated by a number of other tsiqat narrator. The steps that can be taken in tracing the traditions containing syadz, it can simply be done with inventory to convey traditions and compare them, as well as examining the quality rawinya